Penguatan Praktik Pembelajaran Guru Matematika Kabupaten Gowa melalui Kegiatan Identifikasi Kesulitan Mengajar - Nasir, Norma; Khadijah, Khadijah; Wazithah , Mar Athul; Rahayu, Ayu; Liani, Ahyani Mirah (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
The low effectiveness of mathematics learning in secondary schools remains a significant challenge, particularly in relation to teachers’ difficulties in presenting abstract concepts, selecting appropriate instructional strategies, and responding to students’ diverse learning abilities. This condition indicates the need to strengthen teaching practices through reflective and participatory activities that are grounded in real classroom problems. This community service activity aimed to strengthen the teaching practices of mathematics teachers in Gowa Regency through the identification of teaching difficulties as a basis for formulating contextual and applicable learning solutions. The implementation method employed a participatory approach consisting of planning, implementation, and reflection stages. During the implementation stage, teachers were divided into several working groups based on teaching level and teaching experience. Each group conducted focused discussions to identify experienced teaching difficulties, analyze contributing factors, and formulate alternative instructional solutions. Activity data were obtained from group worksheets, discussion results, and group presentations. The activity involved thirty mathematics teachers who were divided into five groups, each consisting of six participants. The results indicated that the first and second groups predominantly identified difficulties in presenting abstract concepts and low student participation, the third group emphasized constraints in selecting instructional models, the fourth group revealed difficulties in learning assessment, and the fifth group highlighted limitations in instructional media. The benefits obtained included increased teachers’ reflective awareness, improved ability to systematically analyze instructional problems, and the development of alternative solutions that were relevant to classroom contexts. This activity confirms that active teacher involvement in identifying teaching difficulties represents an important and innovative approach to strengthening teaching practices based on authentic school needs.